INTERNAL PEOPLE AS THE CORPORATE SOCIAL RESPONSIBILITY (CSR) TARGET AUDIENCE IN THE COVID-19 PANDEMIC ERA: THE CASE OF TOURISM INDUSTRY - Sabar Aritonang Rajagukguk; Mts. Arief; Asnan Furinto; Sri Bramantoro Abdinagoro; Amalia E. Maulana (Malaysian Journal of Business and Economics (MJBE), 2023)
The debate about how CSR be done in a time of crisis has received growing attention in recent years, especially in the wake of the COVID-19 crisis. In line with the previous research that CSR could be done even in times of crisis, the findings revealed that several media to large-sized businesses in Bali have still carried out corporate responsibility programs even the tourism and hospitality industry was arguably hit the hardest. This study uses qualitative research via In-depth Zoom interviews and WhatsApp chat to total of 18 Bali’s medium and large tourism business owners. Theme analysis and comparison were then carried out using the NVivo 12 software. The analysis revealed that CSR during a pandemic is still in accord with Elkington’s framework, which highlighted that internal people are as important CSR target audience. Furthermore, the CSR performed was found to be the bridge to industry survival and sustainability. Business owners realized that social responsibility should start from maintaining their business to foster the internal people. CSR during the pandemic includes dividing tasks to increase effectivity and efficiency in the workplace, upskilling workers, and strong leadership in directing teams to achieve their goals. This study found out that the company survival through genuine internal people management is a relevant approach and should be generalizable in the different industry contexts.